IMPLEMENTASI SOFTWARE AS A SERVICE UNTUK SISTEM E-LEARNING BERBASIS CLOUD COMPUTING MENGGUNAKAN METODE ROCCA - Fadliana, Nurul; Ahyana, Nurul (Teknik Elektro Polsri, 2025)
The adoption of cloud computing has significantly transformed the development of interactive digital learning media by enabling more efficient creation, storage, and distribution of content. This study explores the use of Google Sites as a cloud-based platform for designing and delivering interactive learning materials. The research aims to assess its effectiveness in enhancing accessibility, collaboration, and learner engagement within the digital learning environment at Barombong Maritime Polytechnic. A qualitative approach is used, focusing on usability, functionality, and user experience. The findings reveal that Google Sites provides a flexible, cost-effective, and user-friendly solution for educators to develop and manage online learning resources. The integration of cloud computing into learning media development encourages innovation and improves digital literacy among both educators and learners. This research contributes to the body of knowledge surrounding cloud-based educational tools and offers practical insights for educators seeking to maximize the use of technology in teaching and learning.